Salinity Pattern in Semarang Coastal City: An Overview - Rahmawati, Novi; Marfai, M. A. (Indonesian Journal on Geoscience, 2013)
DOI:Â 10.17014/ijog.v8i2.160Semarang Coastal City is one of cities in Indonesia which has experienced a long-term salt intrusion. Land subsidence and groundwater exploitation were identified as main factors accelerated salt intrusion in this area. Extended salt intrusion into the land from year to year cannot be neglected. Salinity pattern and land use affected by this intrusion must be identified. Salinity pattern could be identified by electrical conductance content. The purposes of this research are: a) to define spatial electrical conductance map from 1995 to 2008 and b) to identify salinity pattern in each land use. Primary data set of electrical conductance measurement in 2004 and 2008 was performed. Secondary data set of electrical conductance was collected in 1995 and 2000. Electrical conductance mapping was assigned by point interpolation using GIS Environment. Land use classification was interpreted from topographical map and IKONOS using GIS Environment. Field check of land use was also done in the study area. Geologically, the area setting consists of Damar, Kalibiuk, and Breccias Formations, where the Damar Formation is the recharge source for groundwater in Semarang City. Based on the result, it can be concluded that the salinity content in groundwater increased from 1995-2008. In 1995, there was only 2.4% of brackish groundwater in Semarang Coastal City, but in 2008, most of area in that region was classified as saline. Land use conversion into built up area increased from 1998 to 2008. The area intruded by salt water increased within 1995, 2004, and 2008 periods. About 68 % of the area contained brackish water and most of the area were built up area in 1995. In 2004, no fresh groundwater found in Semarang Coastal City and the area of brackish groundwater reached 77% and about 23% was saline groundwater which 82% of the built up area included brackish groundwater. In 2008, approximately 55% of Semarang Coastal City was occupied by saline groundwater. About 51% of groundwater built up area was saline.